Communication Media Technology And Social Harmony Construction In The Era Of Society 5.0 A Critical View - Burhan Bungin; Hilda Yunita Wono; Ergita Jeny Ardane Shwari (Institut Teknologi Bisnis AAS Indonesia, 2021)
Abstract—The current media communication technology is growing into an inevitability. This medium can make a world as big as an egg, and it can similarly build a harmony based on its will. The study revealed how communication media technologies are able to build a reality of harmony in society. The study employed a qualitative approach with a post-positivistic paradigm. The research took 5 informants and interviewed them. The results of the study, (1) communication media technology became the main key formed society 5.0. (2) The development of social media in various platforms and with all its advantages caused the mass media mind stream fall one by one. (3) Communication media technology into a medium can bring the far and away close, or in other words create harmony that is switched. (4) Communication media technology has an impact on the occurrence of hoaxes that are actually enemies of the state.